PENERAPAN PIDANA MATI DALAM HUKUM POSITIF DI INDONESIA KAITANNYA DENGAN HAK ASASI MANUSIA (DALAM PERKARA NOMOR 271/Pid.Sus/2016/PN. Mdn jo PERKARA NOMOR 395/Pid.Sus/2016/PT.Mdn) - Rica Gusmarani; Ediwarman Ediwarman; Suhaidi Suhaidi; Mahmud Mulyadi (Universitas Sumatera Utara, 2018)
ABSTRACT The state of emergency of narcotics became the basis of the Indonesian Government's consideration to impose capital punishment on suspected drug cases in this case is Booking and Dealer which in fact have a destructive effect on the future of Indonesian youth. The application of capital punishment, both in Indonesia and countries in the world there are still many opinions that are pros and cons. capital punishment in the positive criminal law in Indonesia is still relevant to apply that in the future the formulation, implementation, and implementation of capital punishment shall pay attention to four important matters. First, capital punishment is no longer a principal punishment, but as a special and alternative criminal act. Secondly, capital punishment may be imposed with a ten-year probation which if the prisoner is liable can be changed with life imprisonment or for 20 years. Third, capital punishment can not be imposed on immature children. Fourth, the execution of capital punishment on pregnant women and a mentally insured person is suspended until the pregnant woman gives birth and the mentally ill prisoner is healed. On the other hand, the death penalty is also intended as a deterrence or detention for criminals, especially narcotics dealers and dealers whose actions can damage the physical and mental generation of young people who are the nation's shoots so that it can threaten the National Resilience of the Indonesian Nation. Keywords: Death Penalty, Narcotics Crime, Human Rights.